Revision of Gentianella austriaca and G. rhaetica ibn Slovenia - Greimler, Josef (Hladnikia (Ljubljana), 2010)
In a revision of Gentianella austriaca and G. rhaetica in Slovenia G. obtusifolia, G. lutescens, and G. rhaetica could be confirmed. Individual plants resemble G. austriaca s.str., however, there is not a single sample consisting entirely of G. austriaca s.str. and most samples were judged as intermediates between G. austriaca and G. rhaetica. Gentianella lutescens, the taxon with the shorter calyx lobes of G. austriaca , and G.rhaetica are the most frequent taxa and the highest number of intermediates were found among these two. Both taxa as well as their intermediates show roughly the same distribution. These geographical patterns do not point to a distinct introgression zone among them in Slovenia.
Keywords: fitogeografija; flora; Slovenia; Slovenija; sviščevci